Relation of Endometrial Hyaluronic Acid with Female Infertility in Women Undergoing Ovarian Stimulation Protocol - Sarab Khlalaf Al-Juboory1 , Mufeda Ali Jwad2 , Muayad Sraibet Abood3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
A comparative prospective study was conducted in the High Institute of Infertility Diagnosis and Assisted Reproductive Technologies, Al-Nahrain University, from September 2019 to March 2020. The aim of the study was to evaluate the level of hyaluronic acid (HA) in endometrial fluid at day of trigger in infertile women whom undergoing ovarian stimulation protocol. The study included a total of 60 women who were selected from those attended the High Institute of Infertility Diagnosis and Assisted Reproductive Technologies. All couples subjected to a full history taking, complete general examination, complete gynecologic examination and infertility workup including: husband’s semen analysis, hormonal analysis, uterine cavity and tubal patency was performed. Different ovulation induction programs were used evaluation of endometrial thickness, pattern, size and number of mature follicles was performed by transvaginal sonography in the 2nd of menstrual cycle and cycle day 11-14 before HCG injection. In this study basal hormonal analysis were performed to the female in the 2nd or 3rd day of the menstrual cycle and study included aspiration of endometrial fluid for determination of hyaluronic acid level by ELISA technique. The study showed that mean of hyaluronic acid was elevated significantly in women received letrozole plus FSH (158.7±19.7 pg/ ml) followed by women received Clomid plus FSH (160.8±13.5 pg/ml) and the lowest mean was recorded in the control group (146.1±26.2 pg/ml). The study showedpositive correlation betweenhyaluronic acid and LH at day of triggering of ovulation in women received Clomid plus FSH (group B). The study showed positive correlation betweenhyaluronic acid and progesterone at day of triggering of ovulation in women received letrozole plus FSH. The study showed positive correlation betweenhyaluronic acid and number of follicles in women after receiving letrozole plus FSH. The study revealed that HA mean was elevated significantly (P< 0.05) in women who became pregnant after stimulation protocol compared with women who failed to be pregnant (164.2 vs. 152.1 pg/ml) as shown in Figure 4). The study also revealed that HA was significantly elevated in women who became pregnant after receiving letrozole + FSH (164.2 pg/ ml) as compared with non pregnant women (152.1 pg/ml) while HA level was non significantly related with pregnancy occurrence after administration of Clomid+FSH. It was concluded that, hyaluronic acid was elevated significantly in women received ovulation simulation drugs and letrozolewas superior to clomiphene as a treatment foranovulatory infertility in women